Critical Analysis of Teachers' Efforts in Developing National Character Through Social Science Learning in Hasanudin Sub-District, Cipari Cluster, Cilacap - Uzlifatul Wijayati (Proceedings Series on Social Sciences & Humanities, 2025)
This research aims to analyse teachers' efforts in developing national character through social studies learning in Gugus Hasanudin, Cipari Sub-district. National character is important to be instilled from an early age to form an attitude of love for the country and awareness of the nation. This research uses a qualitative approach with descriptive method. Data were obtained through observation, interviews, and document analysis. Pre-research results show that teachers have implemented various strategies in social studies learning, but still face challenges such as low awareness of nationalism and the influence of outside cultures. Co-curricular and extra-curricular activities are also not optimal in supporting the strengthening of national character. This research emphasises the importance of more innovative and systematic learning strategies so that students' national character can be formed optimally.